Associations between appetite loss and clinical features as well as inflammatory cytokines in adolescents with major depressive disorder - Liu, Lewei; Zhang, Xi; Xue, Jinyue; Zhao, Lili; Tang, Pei; Tian, Yinghan; Fan, Haojie; Hao, Mingru; Zhao, Xin; Geng, Feng; Mo, Daming; Xia, Lei; et al. (Frontiers in Psychiatry, 2025)
BackgroundAppetite loss is common in major depressive disorder (MDD). However, the psychosocial and biological mechanisms behind appetite loss remain unclear, particularly in the adolescent MDD population. Therefore, this study aimed to examine the links between appetite loss and clinical symptoms as well as inflammatory cytokines levels in this population.MethodsBetween January and December 2021, this study included 171 depressed adolescents. A range of scales were used to assess the patients’ clinical symptoms, including depression severity, negative life events, insomnia, and alexithymia. Additionally, plasma inflammatory cytokines levels were measured, including interleukin (IL)-1β, IL-6, IL-10, IL-17A and tumor necrosis factor-α (TNF-α).ResultsThe prevalence of appetite loss among adolescents with MDD was as high as 76.0%. Univariate analyses showed that patients with appetite loss had higher scores of the Hamilton Depression Scale (HAMD), interpersonal relationships, study pressure, punishment, sense of loss, the Insomnia Severity Index Scale (ISI) and difficulty identifying feelings, as well as higher levels of Log IL-6 (all p < 0.05) Furthermore, regression analyses revealed that appetite loss was independently associated with HAMD score (OR = 1.158, 95% CI = 1.091-1.229, p < 0.001), punishment score (OR = 1.117, 95% CI = 1.039-1.201, p = 0.003), and Log IL-6 level (OR = 5.041, 95% CI = 1.137-22.344, p = 0.033).ConclusionAdolescents with MDD face an elevated risk of appetite loss, which may correlate with clinical symptoms such as depression severity and negative life events, as well as elevated IL-6 level. Healthcare professionals should target these risk factors, including inflammation, to mitigate appetite loss.